Ceramide contributes to pathogenesis and may be targeted for therapy in VCP inclusion body myopathy. (7th January 2021) - Weiss, Lan; Jung, Kwang-Mook; Nalbandian, Angele; Llewellyn, Katrina; Yu, Howard; Ta, Lac; Chang, Isabela; Migliore, Marco; Squire, Erica; Ahmed, Faizy; Piomelli, Daniele; Kimonis, Virginia
Abstract: Knock-in homozygote VCP R155H/R155H mutant mice are a lethal model of valosin-containing protein (VCP)-associated inclusion body myopathy associated with Paget disease of bone, frontotemporal dementia and amyotrophic lateral sclerosis. Ceramide (d18:1/16:0) levels are elevated in skeletal muscle of the mutant mice, compared to wild-type controls. Moreover, exposure to a lipid-enriched diet reverses lethality, improves myopathy and normalizes ceramide levels in these mutant mice, suggesting that dysfunctions in lipid-derived signaling are critical to disease pathogenesis. Here, we investigated the potential role of ceramide in VCP disease using pharmacological agents that manipulate the ceramide levels in myoblast cultures from VCP mutant mice and VCP patients. Myoblasts from wild-type, VCP R155H/+ and VCP R155H/R155H mice, as well as patient-induced pluripotent stem cells (iPSCs), were treated with an inhibitor of ceramide degradation to increase ceramide via acid ceramidase (ARN082) for proof of principle. Three chemically distinct inhibitors of ceramide biosynthesis via serine palmitoyl-CoA transferase (L-cycloserine, myriocin or ARN14494) were used as a therapeutic strategy to reduce ceramide in myoblasts. Acid ceramidase inhibitor, ARN082, elevated cellular ceramide levels and concomitantly enhanced pathology. Conversely, inhibitors of ceramide biosynthesis L-cycloserine, myriocin and ARN14494 reduced ceramide production. The results point to ceramide-mediated signaling as a key contributor to pathogenesis in VCP disease and suggest that manipulating this pathway by blocking ceramide biosynthesis might exert beneficial effects in patients with this condition. The ceramide pathway appears to be critical in VCP pathogenesis, and small-molecule inhibitors of ceramide biosynthesis might provide therapeutic benefits in VCP and related neurodegenerative diseases.